(untitled) (The Review of Diabetic Studies, 2025)
This study aims to describe the current reality of the distribution of ambulance centers in urban and rural areas in the Kingdom of Saudi Arabia highlighting the degree of balance and equity in the geographical allocation of these centers The study adopts a descriptive research approach that focuses on analyzing existing information and documented data related to ambulance services without introducing experimental or analytical variables The methodology relies primarily on comparison with previous studies official reports and related research in the field of emergency medical services to identify similarities differences and emerging patterns in service distribution The study reviews national and regional literature addressing emergency medical coverage response times population density and geographic challenges affecting ambulance center placement Particular attention is given to the contrast between urban areas which often benefit from higher population density and better infrastructure and rural areas which may face limitations related to distance terrain and resource availability By comparing findings from earlier research the study seeks to describe the extent to which current distribution practices meet community needs and support timely emergency response The results of this descriptive review are expected to provide a clearer understanding of existing strengths and gaps in ambulance center distribution contributing to informed decision-making and future planning The study concludes by emphasizing the importance of evidence-based distribution strategies to enhance equity accessibility and overall efficiency of ambulance services across both urban and rural regions in the Kingdom of Saudi Arabia .